Critical Thinking in the Iranian EFL Context: A Systematic Review - Shaho Hoorijani; Hossein Heidari Tabrizi (Research in English Language Pedagogy)
Critical thinking has been studied within different educational and professional settings as one of the renowned learning and innovation skills of the 21st century. However, the degree to which it is operationally defined, taught, and assessed in Iran is poorly documented. This complicates efforts to develop critical thinking disposition studies and assessment tools in the Iranian EFL context. In today’s EFL contexts, it is a common belief that having critical thinking dispositions among learners and synthesizing them with action learning approaches provide them opportunities for better understanding and enhancing their new knowledge, especially in argumentative writing. Therefore, most educational programs put an effort into developing such potential among EFL learners. This paper aimed to systematically review critical thinking disposition studies in the Iranian EFL context. Firstly, a number of definitions, along with the dimensions of the concept from various scholars' viewpoints, are presented. Secondly, the typical features of critical thinkers and what resources they need are introduced. Finally, the issue from both theoretical and pedagogical standpoints was reviewed to understand the use of critical thinking in the education field in the Iranian EFL context. It is hoped that this systematic review sheds light on the gap between pedagogical rhetoric and classroom practices due to the lack of CT attention implications for future research for conducting CT-integrated pedagogies in the Iranian EFL context.